The robustness of output measures in property-liability insurance efficiency studies - Leverty, J. Tyler; Grace, Martin F. (Journal of Banking & Finance, 2010)
We empirically examine two methods for measuring output in property-liability insurer efficiency studies: the value-added approach and the “flow” (or financial intermediation) approach. The approaches are not mutually consistent. The value-added approach is closely related to traditional measures of firm performance, but the flow approach is not. In addition, efficient value-added approach firms are less likely to go insolvent, while firms characterized as efficient by the flow approach are generally more likely to fail. We also find that the theoretical concern regarding the value-added approach’s use of losses as a measure of output is not validated empirically.